"I Live Here": How Residents of Color Experience Racialized Surveillance and Diversity Ideology in a Liberal Predominantly White Neighborhood. (June 2022) - Lowe, Maria R.; Carrola, Madeline; Cortez, Dakota; Jalufka, Mary
In many liberal predominantly white neighborhoods, white residents view their communities as inclusive yet they also engage in racialized surveillance to monitor individuals they perceive as outsiders. Some of these efforts center on people of color in neighborhood open spaces. We use a diversity ideology framework to analyze this contradiction, paying particular attention to how residents of color experience racialized surveillance of their neighborhood's publicly accessible parks and swimming pools. This article draws on data from neighborhood documents, neighborhood digital platforms, and interviews with residents of a liberal, affluent, predominantly white community that was expressly designed with public spaces open to non-residents. We find that resident surveillance of neighborhood public spaces is racialized, occurs regularly, and happens in person and on neighborhood online platforms where diversity as liability rhetoric is conveyed using colorblind discourse. These monitoring efforts, which are at times supported by formal measures, impact residents of color to varying degrees. We expand on diversity ideology by identifying digital and in-person racialized surveillance as a key mechanism by which white residents attempt to enforce racialized boundaries and protect whiteness in multiracial spaces and by highlighting how Black and Latinx residents, in particular, navigate these practices.